Consumers’ Willingness to Pay for Gamy Salt in Jabodetabek - Khalda Tsaniaty Halimah; Tursina Andita Putri (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2024)
Seaweed, being an abundant resource, has the potential to be processed into raw material for salt. This potential is supported by the high demand for salt consumption and the serious problem of hypertension in Indonesia. Consuming salt made from seaweed can be an alternative with low sodium content, which can help manage hypertension. Currently, the salt made from seaweed that is available to be purchased is Gamy salt. However, Gamy salt is more expensive than other low-sodium salts. This research aims to estimate the amount of consumers’ willingness to pay for Gamy salt and identify factors that influence their willingness to pay. The analytical methods used in this research include descriptive analysis, Contingent Valuation Method, and logistic regression. The research involved 103 respondents aged 30 years and above, residing in Jabodetabek, and having a history or risk of hypertension. The results indicate that the average willingness to pay for Gamy salt is Rp17,873.79 per 100 grams. Factors that significantly influence consumers to pay an extra price for Gamy salt are income, knowledge regarding seaweed salt, and health awareness.